Clindamycin to reduce preterm birth in a low resource setting: a randomised placebo‐controlled clinical trial. (25th June 2018) - Bellad, MB; Hoffman, MK; Mallapur, AA; Charantimath, US; Katageri, GM; Ganachari, MS; Kavi, A; Ramdurg, UY; Bannale, SG; Revankar, AP; Sloan, NL; Kodkany, BS; et al.
Abstract : Objective: To determine whether oral clindamycin reduces the risk of preterm birth (PTB) in women with abnormal vaginal microflora as evidenced by a vaginal pH ≥5.0. Design: Randomised double‐blind placebo‐controlled trial. Setting: Rural southern India. Population: Pregnant women with a singleton fetus between 13 +0/7 weeks and 20 +6/7 weeks. Methods: Pregnant women were recruited during prenatal visits in Karnataka, India, from October 2013 to July 2015. Women were required to have a singleton fetus between 13 +0/7 weeks and 20 +6/7 weeks and an elevated vaginal pH (≥5.0) by colorimetric assessment. Participants were randomised to either oral clindamycin 300 mg twice daily for 5 days or an identical‐appearing placebo. Main outcome measures: The primary outcome was the incidence of PTB, defined as delivery before 37 +0/7 weeks. Results: Of the 6476 screened women, 1727 women were randomised (block randomised in groups of six; clindamycin n = 866, placebo n = 861). The demographic, reproductive, and anthropomorphometric characteristics of the study groups were similar. Compliance was high, with over 94% of capsules being taken. The rate of PTB before 37 weeks was comparable between the two groups [clindamycin 115/826 (13.9%) versus placebo 111/806 (13.8%), between‐group difference 0.2% (95% CI −3.2 to 3.5%, P = 0.93)], as was PTB at less than 34 weeks [clindamycin 40/826 (4.8%) versus placebo group 37/806 (4.6%), between‐group difference 0.3% (95% CI −1.8 to 2.3%, P = 0.81)]. No differences were detected in the incidence of birthweight of<2500 g, <1500 g, miscarriage, stillbirth or neonatal death. Conclusion: In this setting, oral clindamycin did not decrease PTB among women with vaginal pH ≥5.0. Tweetable abstract: Oral clindamycin between 13 +0/7 and 20 +6/7 weeks does not prevent preterm birth in women with a vaginal pH ≥5.0. Tweetable abstract: Oral clindamycin between 13 +0/7 and 20 +6/7 weeks does not prevent preterm birth in women with a vaginal pH ≥5.0.